Factors associated with false positive results in serological testing for syphilis using EIA among children - Liu, Jiaqi; Chen, Qianqian; Zhao, Guangchao; Fan, Xuzhou; Wang, Wei (Frontiers in Pediatrics, 2025)
ObjectivesThe issue of biological false positives in syphilis diagnosis is gaining attention. However, limited focus exists on false positives in syphilis tests among younger populations. This study investigates the epidemiological characteristics and influencing factors of false positive serological test results for syphilis in children.MethodsA retrospective study was conducted on the serological test results, demographic, clinical, and laboratory characteristics of children in Jinling Hospital from 2017 to 2022.ResultsThis study included 18 cases of false positive syphilis results. Children aged 5–9 years had a higher proportion of false positives compared to those with negative results (p < 0.001). The prevalence of adenoid hypertrophy (AH) in children with false positives was 38.89%, significantly higher than in those with negative results (p < 0.0001). The results of syphilis antibodies detection by enzyme-linked immunosorbent assay (EIA) in false positive cases, negative cases, and true positive cases were significantly different (p < 0.0001). Children with false-positive syphilis results had significantly higher systemic immune-inflammation index (SII), fibrin degradation products (FDP), and platelet (PLT) levels than those with negative results (p < 0.05). Compared to true-positive cases, false-positive cases showed lower systemic inflammation response index (SIRI) and neutrophil-to-lymphocyte ratio (NLR) but higher lymphocyte-to-monocyte ratio (LMR), antithrombin III (AT-III), and PLT levels (p < 0.05). Furthermore, among children with false-positive serological test results for syphilis, certain coagulation parameters, such as FDP, D-dimer (DD), AT-III, and PLT, were found to be elevated (p < 0.05). Univariate logistic regression analysis revealed that age (OR = 0.852, 95% CI: 0.766, 0.948), AH (OR = 20.10, 95% CI: 5.361, 79.53), APTT (OR = 0.804, 95% CI: 0.658, 0.977), FDP (OR = 1.722, 95% CI: 1.234, 2.416), AT-III (OR = 1.071, 95%CI: 1.030, 1.121), and PLT (OR = 1.008, 95%CI: 1.003, 1.013) were risk factors associated with the occurrence of a false positive reaction in syphilis serology (p < 0.05).ConclusionsIn the assessment of false-positive syphilis test results, age and inflammatory marker data exhibit reference value. AH and partial coagulation function indices are risk factors for false positive syphilis serology results in children. Therefore, it is crucial for clinical and laboratory doctors to pay close attention to positive results for syphilis in such cases.